Sensitive detection of Xanthomonas oryzae Pathovars oryzae and oryzicola by loop-mediated isothermal amplification - Lang, Jillian M.; Langlois, Paul; Nguyen, Marian Hanna R.; Triplett, Lindsay R.; Purdie, Laura; Holton, Timothy A.; Djikeng, Appolinaire; Vera Cruz, Casiana M.; Verdier, Valérie; Leach, Jan E. (American Society for Microbiology, 2014)
Molecular diagnostics for crop diseases can enhance food security by enabling the rapid identification of threatening pathogens and providing critical information for the deployment of disease management strategies. Loop-mediated isothermal amplification (LAMP) is a PCR-based tool that allows the rapid, highly specific amplification of target DNA sequences at a single temperature and is thus ideal for field-level diagnosis of plant diseases. We developed primers highly specific for two globally important rice pathogens, Xanthomonas oryzae pv. oryzae, the causal agent of bacterial blight (BB) disease, and X. oryzae pv. oryzicola, the causal agent of bacterial leaf streak disease (BLS), for use in reliable, sensitive LAMP assays. In addition to pathovar distinction, two assays that differentiate X. oryzae pv. oryzae by African or Asian lineage were developed. Using these LAMP primer sets, the presence of each pathogen was detected from DNA and bacterial cells, as well as leaf and seed samples. Thresholds of detection for all assays were consistently 10 4 to 10 5 CFU ml −1 , while genomic DNA thresholds were between 1 pg and 10 fg. Use of the unique sequences combined with the LAMP assay provides a sensitive, accurate, rapid, simple, and inexpensive protocol to detect both BB and BLS pathogens.